Correlation of Coronary Heart Disease Patient Assessments of Chronic Illness Care and Quality of Care Procedures: Kakovost oskrbe v odnosu na oceno kakovosti vodenja kronične bolezni bolnikov s koronarno boleznijo - Tušek-Bunc, Ksenija; Petek-Šter, Marija; Petek, Davorina (Acta Medico-Biotechnica, 2021)
Purpose: Patient-centered assessment of chronic illness care is replacing the assessment of satisfaction, which does not cover all dimensions of care. Patient assessments reflect both the quality of chronic illness care and provide feedback to healthcare workers about their work. The study aim was to investigate the patient-centered assessment of coronary heart disease (CHD) patients and its correlation with the care that was delivered. Methods: This cross-sectional study evaluated data obtained from the patient medical records and surveyed patients using the Patient Assessment of Chronic Illness Care (PACIC) questionnaire. A descriptive analysis of the overall and domain-specific responses to the PACIC questionnaire was conducted and the association of the results with delivery of care data in the patient records was determined by Pearson’s correlation coefficient. Results: The study sample included 768 of 1080 CHD patients (71,1%) at 36 family medicine practices who completed the PACIC questionnaire. The mean age of the respondents was 68.3 ± 10.7 years and the overall PACIC score was 3.3 ± 0.9. The highest PACIC scores were delivery system design (3.7), patient activation (3.7), and problem solving (3.6). Follow-up received the lowest score (2.8). Quality of delivered care and PACIC scores were correlated (r = 0.10, p = 0.009). Conclusions: CHD patients highly rated all aspects of chronic care included in the PACIC questionnaire. They were least satisfied with the follow-up and coordination aspects of chronic care. The process indicators of care were positively correlate with patient assessment of care.